Penggunaan Tanda Tangan Elektronik dalam Pengajuan Pembiayaan berdasarkan Prinsip Syariah - Aulia Delvina (Universitas Widyatama, 2019)
The development of the Sharia Banking Industry is now very rapidly marked by the increasing prevalence of Sharia Commercial Banks. Of course this is in line with business competition, Islamic banks are required to always prioritize better quality services, but are also bound by the good provisions stipulated in the legislation and the Financial Services Authority Regulation (POJK), one of the efforts to improve services is by the Use of Electronic Signatures in Submission of Financing based on sharia principles. The reason for the launch of the Electronic Signature service in the Filing of Financing is to accommodate service users who want convenience in banking transactions. Electronic Signature Service in Submission of Sharia-based Financing in addition to providing easier offers and schemes also provides certain restrictions on the certification of electronic signatures. Demand for the Use of Electronic Signatures in Submission of Sharia-based Financing that continues to increase is supported by the market share of service users from the Indonesian community, the majority of whom are Muslims.Regulation of the Financial Services Authority (POJK) and Sharia Compliance.